India-Canada Relations: A View on Geopolitical, Geoeconomic Convergence and Divergence - Bragta, Sanjeev Kumar (Technium Social Sciences Journal, 2022)
The relationship between India-Canada is built upon a mutual respect for democracy, multiculturalism and people to people contact over the period of time. Despite of this, India and Canada relationship is yet to develop its full potential. The present article tries to examine and analyses the geopolitical relations and bilateral engagement between India-Canada and its geoeconomic potential in the present century. The various efforts were made to conclude a Comprehensive Economic Partnership Agreement (CEPA) between the two nations on the lines of a Free Trade Agreement (FTA) with commitments to tariff reductions and reforms in the commercial environment. Despite of few irritants, both the country started moving towards greater trade cooperation and collaboration. It is against this backdrop the research article aims to analyze the degree of convergence and divergence of geopolitical and geoeconomic issues that have affected New Delhi’s interest in seeking a broader relationship with Ottawa. Further, the paper will try to examine the other factors in cementing the multilateral collaboration and cooperation between the two nations in the present century.